Nuclear transfer and reprogramming in fish - Wang, Xue-Geng; Zhu, Zuo-Yan; Sun, Yong-Hua; Zhao, Jue (Yíchuán, 2013)
As an important sub-field in the study of animal cloning, fish nuclear transfer was first established in the early 1960s by Chinese embryologists. Due to its advantages, zebrafish has become a unique animal model to study the mystery of reprogramming in nuclear transfer. This article summarizes the history and current situation in fish nuclear transfer technology and discusses the factors that may influence the development of the cloned embryos. A comprehensive understand-ing of the mechanism for epigenetic modification following nuclear transfer, such as genomic DNA methylation and histone acetylation and/or methylation, will likely increase the success rate and eventually lead to the future freedom of cloning technique.